Produção de lacases por Pleurotus ostreatus e o uso da biorremediação e adsorção para tratamento de poluentes via biomassa residual - Nunes, Elaine Sousa (2022)
The contaminants of effluents with domestic and industrial releases have been proven in several regions of the planet. In the face of outbreaks caused by flaviviruses the use of repellents has grown significantly, as well as synthetic dyes, because they are widely used in the textile industry and bisphenol A, because it is found in different commercial polymers, are commonly found in pollutants keeping present in waters generating possible harmful effects. Conventional effluent treatment processes have low chemical removal efficiency and are expensive. In view of this, the objective of this study was the development and evaluation of methodologies for the treatment of effluents contaminated with the active ingredient of repellents, icairidina, red textile dye Drimaren CL-5B and bisphenol A (BPA) by using açaí residue as adsorbent material and/or bioremediation with the lacase produced from the white decomposition fungus Pleurotus ostreatus using as enzymatic inducer the solid residues of acai, pineapple, mexerica and pequi. The enzymatic production with the residues of açaí and pineapple obtained an activity of 1139 UmL-1 and 1031 UmL-1 respectively. Remediation was efficient for BPA, being able to bioremediate up to 100 % of the compound, but it was ineffective for icariride. However, açaí revealed high adsorptive capacity, reaching to fully adsorb bisfinel A, more than 50 % of iridin and more than 70 % of the dye when in a synthetic sample and 40 % in an industrial sample, demonstrating a promising methodology.